Spreading patterns, prognostic factors and treatment outcomes of nasopharyngeal papillary adenocarcinoma and salivary gland‐type carcinomas. (4th February 2016) - Liu, L.Z.; Zhang, Y.M.; Chen, Y.; Li, L.
Abstract : Objectives: In this study, we aim to analyse the different spreading patterns, prognostic factors and treatment outcomes of nasopharyngeal papillary adenocarcinoma (NPAC) and salivary gland‐type carcinomas (NPCs). Design, setting and participant: The current study report on a retrospective analysis of oncologic outcome of 76 pathologically confirmed consecutive cases of nasopharyngeal adenocarcinomas (NAC), including 31 NPAC, 33 adenoid cystic carcinomas (ACC) and 12 mucoepidermoid carcinomas (MEC). Main outcome measure: Overall survival rates (OS) and disease‐free survival rates (DFS). Results: In 12 patients with cranial nerve (CN) palsy, there were ACC ( n = 9), NPAC ( n = 2) and MEC ( n = 1) ( P = 0.016). CT‐/MRI‐detected CN involvements were found in 22 patients. Lymph node metastasis was observed in 25.8% of NPAC ( n = 8), 12.1% of ACC ( n = 4) and 8.3% of MEC ( n = 1). Significant differences were observed in 5‐year overall survival (OS) and disease‐free survival (DFS) rates between patients with and without CT‐/MRI‐detected CN involvement ( P = 0.002 and P = 0.002, respectively), and similar results were found between patients with and without lymph node metastasis ( P = 0.002 and P = 0.018, respectively). In 37 patients with early‐stage disease (stages I–II), significant differences were observed in 5‐year OS and DFS rates between the surgical and non‐surgical treated groups ( P = 0.031 and P = 0.012, respectively). In 39 patients with advanced‐stage disease (stages III–IV), significant or marginally differences were observed in DFS and OS between the chemoradiotherapy and non‐chemoradiotherapy groups ( P = 0.007 and P = 0.062, respectively). Conclusions: ACC has a higher CN invasion than NPAC and MEC, and NPAC has the highest rate of lymphatic metastases. CT‐/MRI‐detected CN involvements and lymph node metastasis indicate a negative impact on the prognosis. The outcome of surgical patients in our series is encouraging in early‐stage NPAC and NPCs, and chemoradiotherapy may be the optimal treatment for the advanced‐stage patients.